The role of Physiotherapy in the rehabilitation of post-COVID-19 patients: an integrative review (Research, Society and Development, 2021)
COVID-19 is an infectious disease caused by SARS-CoV-2, making it a global emergency. Coronaviruses can cause mild or severe symptoms, depending on the degree of infection, such as dry cough, fever, myalgia and breathing difficulties. Its transmission happens quickly, through respiratory droplets, which can be expelled through speech, sneezing and coughing, even by contaminated objects. The severity of the disease is related to individuals in the risk group, which are individuals affected by complications of COVID-19: such as smokers, obese people, people with cardiovascular disease, underlying comorbidities, liver disease, cancer, etc. In addition to diseases of the respiratory system. In this pandemic context, the physical therapy approach proved to be effective and of great importance, both in the beginning of treatment and in the recovery phase of the infection caused by COVID-19. Objective: Conduct a literature review on the role of Physiotherapy in the rehabilitation of post-COVID-19 patients. Methodology: study of literature review, the databases chosen for the research were: Academic Google, PubMed and Science Direct. Inclusion criteria were research addressing COVID-19, focusing on physical therapy rehabilitation in post-COVID-19 patients, published between 2020 and 2021, in Portuguese and English. Results: After analyzing and discussing the data, 08 studies showed positive results in the rehabilitation process of the post-COVID patient. Final Considerations: Concluding that Physiotherapy has a main role in improving respiratory function and consequently in the patient's quality of life.